Potential role of lysine acetylation in the stepwise adaptation of Candida albicans to fluconazole - Nana Song; Yuying Huang; Xiaowei Zhou; Dongmei Li; Weida Liu; Xiaofang Li (Microbiology Spectrum)
ABSTRACT Candida albicans is an opportunistic fungal pathogen capable of causing superficial mucosal and systemic infections, sometimes leading to life-threatening conditions. The increasing resistance of C. albicans to azole antifungals has become a significant challenge in clinical treatment. Lysine acetylation (KAc) is a well-studied post-translational modification that plays crucial roles in various biological processes. However, its impact on antifungal resistance in C. albicans remains poorly understood. Five strains of C. albicans isolated from the same patient, representing different stages of acquired fluconazole resistance in vivo, were used in this study to investigate the potential regulatory mechanism of KAc on the development of azole resistance in C. albicans. Quantitative proteomic analysis using tandem mass tag (TMT) labeling, acetylation enrichment, and liquid chromatography-mass spectrometry (LC-MS) was conducted on these five strains. We divided all strains into four comparison groups and identified a total of 1,796 lysine acetylation sites across 938 proteins, with quantitative data available for 1,314 acetylation sites in 712 proteins. Analysis of 155 significantly differentially modified sites revealed that the acetylation levels of key proteins involved in the conversion of pyruvate to acetyl-CoA for entry into the tricarboxylic acid (TCA) cycle for energy production were initially decreased and then increased during the acquisition of fluconazole resistance. Additionally, the acetylation levels of proteins involved in ribosome synthesis, translation processes, and amino acid synthesis were found to increase. Therefore, lysine acetylation in C. albicans may contribute to azole resistance by regulating energy metabolism and protein synthesis.IMPORTANCECandida albicans, an opportunistic fungal pathogen, presents significant clinical challenges due to its escalating resistance to azole antifungals, especially fluconazole. This study investigates the role of lysine acetylation in the development of azole resistance using multiple strains isolated from a single patient with varying resistance levels. Through advanced proteomic analysis, we identified numerous lysine acetylation sites on proteins involved in key metabolic pathways. The results revealed a dynamic change in the acetylation of proteins related to energy metabolism — specifically, those connecting pyruvate to the tricarboxylic acid cycle—which correlated with the evolution of resistance. Additionally, increased acetylation was observed in proteins linked to ribosome synthesis and translation processes. These findings suggest that lysine acetylation is crucial for regulating metabolic and protein synthesis pathways, potentially influencing azole resistance in C. albicans.